Performing Society: Pursuing Creativity and Criticality in Secondary ELA (LEARNing Landscapes, 2020)
As an English Language Arts teacher, I have experienced cost-effective approaches replacing the actual “arts” of ELA (Trend, 1992). This article explores how Surrealist-oriented pedagogies could restore imaginative freedom and deconstruct conceptual barriers (normative standards, curricular constraints, and status quo power relations) in secondary ELA. I will also examine how we can use Surrealism as a political and pedagogical model to treat societal problems mirrored in ELA classrooms. Surrealist-oriented pedagogies could enable students to experiment with social issues and develop senses of agency and voice that reflect awareness of contemporary society while simultaneously building their ELA skills.
Keywords: Surrealism; Education; Aesthetics; Critical Pedagogy; Neoliberalism